Investigating the population structure and genetic differentiation of livestock guard dog breeds. (14th January 2018) - Bigi, D.; Marelli, S.P.; Liotta, L.; Frattini, S.; Talenti, A.; Pagnacco, G.; Polli, M.; Crepaldi, P.
Abstract : Livestock guarding dogs are a valuable adjunct to the pastoral community. Having been traditionally selected for their working ability, they fulfil their function with minimal interaction or command from their human owners. In this study, the population structure and the genetic differentiation of three Italian livestock guardian breeds (Sila's Dog, Maremma and Abruzzese Sheepdog and Mannara's Dog) and three functionally and physically similar breeds (Cane Corso, Central Asian Shepherd Dog and Caucasian Shepherd Dog), totalling 179 dogs unrelated at the second generation, were investigated with 18 autosomal microsatellite markers. Values for the number of alleles per locus, observed and expected heterozygosity, Hardy–Weinberg Equilibrium, F stats, Nei's and Reynold's genetic distances, clustering and sub-population formation abilities and individual genetic structures were calculated. Our results show clear breed differentiation, whereby all the considered breeds show reasonable genetic variability despite small population sizes and variable selection schemes. These results provide meaningful data to stakeholders in specific breed and environmental conservation programmes.